(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate physiological seeds quality of four soybean cultivars during storage, under controlled and uncontrolled conditions. Seeds of Brasmax Lança IPRO, Brasmax Raio IPRO (está diferente do Material e Médtodos), Pioneer 95y52 and TMG 7062 IPRO cultivars were stored in controlled (20 ± 1.2 °C) and uncontrolled (producer’s warehouse) environments and the following traits were assessed: percentage of germination (GERM), germination speed index (GSI), germination speed (GS) and accelerated aging (AA) at 0, 60, 120 and 180 days of storage. Covariance matrices structure of storage time was tested through repeated measures analysis, adopting a bifactorial model. Data were submitted to ANOVA (α=5%) and when the means presented significant differences, regression analysis and Scott-Knott test (α=5%) were performed. Differences in soybean seeds physiological quality are not related to storage environment. Lança cultivar was the most tolerant to storage, while Ray and TMG 7062 cultivars were more sensitive.